MIKAN GLOBE MT: An Interactive World Map featuring Seamless Map Projection and Guaranteed Visibility - OKAMOTO, Makoto; MATSUYAMA, Katsutsugu (Journal of the Society for Art and Science, 2009)
This paper describes the research and development of a new tool for visualizing world maps. The developers anticipate this tool will provide a better grasp of structures and enable an improved understanding of features from multiple viewpoints. The following needs were identified on the basis of interviews with subjects who are likely users of map software: overhead views and true-to-life views; side-by-side comparison of arbitrarily selected locations; and context awareness. The software was designed to satisfy these requirements by incorporating a new algorithm, resulting in a package with distinctly different characteristics from those that are browsed in a directly geometric fashion. In this paper, we propose a viewing system that allows the user to switch seamlessly between different geographical projections and a multi-focus view displaying method by parameter adjustment and split screen. The effectiveness of this approach is validated in a survey of subjects using this mapping software.